Whose Language Is Legit? Intersections of Race, Ethnicity, and Language. (March 2016) - Zisselsberger, Margarita; Collins, Kristina
This case describes St. Lucy School, a K-8 elementary school in a mid-sized urban center. St. Lucy has traditionally served African American students. In the past 10 years, the neighborhood has experienced a significant shift in population, such that many Latino/a families are now entering the school. In response to these changes, the school administration made the decision to transition into a fully bilingual school. As the school has begun to treat the Spanish language as an asset, however, tensions have arisen regarding why African American English (AAE) has not been—nor is currently—treated as an asset as well. In addition, there are tensions around the varieties of Spanish used, revealing different attitudes and beliefs about non-standard varieties of Spanish.